Anti-DFS70 Antibodies Are Associated With Proliferative Lupus Nephritis and Renal Pathological Activity - Chen, Dandan; Zhao, Li; Dai, Yingxin; Du, Fang; Li, Enling; Niu, Xiangyu; Wang, Zhiqing; Zheng, Bing; Lu, Liangjing (Frontiers in Immunology, 2022)
Objective The significance of anti-dense fine speckles 70 (DFS70) antibodies in systemic lupus erythematosus (SLE) is still unclear, especially in lupus nephritis (LN) patients. We investigated the prevalence, clinical and pathological relevance of anti-DFS70 antibodies in LN patients. Methods Anti-DFS70 antibodies were measured using enzyme-linked immunosorbent assays in 377 biopsy-proven LN patients, 268 non-LN SLE patients, 232 chronic kidney disease (CKD) patients, and 78 healthy individuals (HI). Demographic, clinical, and pathological parameters were compared between LN patients with and without anti-DFS70 antibodies. Stepwise multivariable logistic regression was performed to identify covariates associated with anti-DFS70 antibodies. Results The prevalence of anti-DFS70 antibodies in LN (19.6%) was comparable to non-LN SLE patients (19.8%, P=0.9630), but was significantly higher than CKD patients (13.4%, P=0.0468) and HI (9.0%, P=0.0252). Using multivariable logistic regression analysis, the titer of anti-double-stranded DNA (dsDNA) antibodies (adjusted odds ratio=1.002, 95% confidence interval 1.001-1.003, P=0.004) was associated with positive anti-DFS70 antibodies in LN patients. In addition, anti-DFS70 antibodies were more prevalent in proliferative LN (22.0%, 68/309) compared to membrane LN patients (10.2%, 6/59, P=0.0376). Furthermore, LN patients with positive anti-DFS70 antibodies had significantly higher activity index (AI) compared to patients who were negative (8.0 vs 6.0, P=0.0131). However, the chronicity index was similar between the groups (3.0 vs 3.0, P=0.8412). Conclusion Anti-DFS70 antibodies were not associated with LN development in SLE patients but were associated with anti-dsDNA antibodies, proliferative LN, and renal AI. This suggests their potential to serve as a non-histological biomarker for LN subclass and activity status.